The Importance of the Work Environment as a Mediation on Employee Performance: Affected by Work Life Balance - Djoko Soelistya (Budapest International Research and Critics University, 2022)
In today's business world, many companies experience several obstacles in their business, especially in the world of animal feed business activities. And the prospect of the 2021 poultry industry cannot be separated from the condition of economic fundamentals, as stated by the Government and also Bank Indonesia (BI), which previously experienced a decline, it is hoped that there is optimism that the economy will recover in the second quarter of 2021, growing 5 percent, while BI's projection is around 4. 8-5.8 percent. However, the Indonesian economy has not been able to fully recover, the movement of the economy still depends on its human resources in carrying out its business activities, and also there are problems within the company, such as the workload given by the company to employees and the supervision of their work in operations. Companies in general have a goal to earn operating profits and strive to maintain and develop the viability of the business itself. HR is very necessary in this case to support employee performance so that it remains on the corridor to achieve organizational goals. This study uses a quantitative approach that has a population of all employees and the sample is 75 respondents, which is called a saturated sample. In this study the results show (1) there is a significant effect of Work Life Balance (X1) on employee performance (Y); (2) there is a significant effect of Work life Balance on the Work Environment (Z) on employee performance (Y); (3) there is a significant influence of the Work Environment (Z) on employee performance; (4) Work Life Balance can improve employee performance directly and preferably through the Work Environment as a mediating variable.